Comparative study of crossed pinning v/s lateral pinning in paediatric supracondylar humerus fractures - Sharma, Dev Krishan; Solanki, Mahendra; Solanki, Sunita; E. P., Akshaj (International Journal of Research in Orthopaedics, 2024)
Background: Closed reduction and percutaneous pinning are the preferred management of supracondylar humerus fractures in children, but the preference of pinning pattern needs more research. A prospective comparative interventional study was undertaken to compare the stability of fixation, functional outcome and neurovascular complications between crossed pinning and lateral pinning in Gartland type 2 and type 3 fractures. Methods: 60 patients of age group 2 to 12 years with Gartland’s type 2 and 3 fracture were randomized into 2 groups- lateral pinning (n=30) and crossed pin fixation (n=30). Intraoperative parameters were compared, post operative ulnar nerve palsy and serial range of motion were assessed. At 3 month follow up, outcome was assessed using Flynn criteria. The results were compared and analysed. Results: There were 2 cases (3.3%) of iatrogenic ulnar nerve injury in crossed pinning group and none in lateral pinning group. Lateral group had more cases with excellent Flynn rating. The mean loss of range of motion and the mean loss of carrying angle was significantly lower for lateral method. Conclusions: Lateral pinning provides, better functional outcome along with comparable stability without the risk of iatrogenic ulnar nerve injury.